Tax Certification and Tax Compliance in the South West, Nigeria - Alade, Muyiwa; Salami, Modupe (Archives of Business Research, 2024)
Purpose: Despite the efforts of Federal and State governments in Nigeria to employ administrative tools to improve tax compliance, the nation is still being bedeviled with the issue of low tax compliance, leading to the inability of the government to finance their statutory responsibilities due to the paucity of funds. Therefore, this study investigated the effects of tax certification on tax compliance in South-west Nigeria. Design/methodology/approach: A survey research design was opted for to obtain primary data from a sample size of 400 participants drawn from a population of 1,194 using Slovin’s formula and purposive sampling technique. Both descriptive and influential statistics were performed. Partial Least Square (PLS) regression was used to analyze the data. Findings: The results show that tax certification (β = 0.261; p-value = 0.044) has a positive effect on tax compliance in South-West Nigeria, which is statistically significant at 0.05 level. Based on these findings, the study concluded that tax certification is an essential tax compliance tool in South West, Nigeria. Research limitations/implications: The results imply that improved efforts in issuing tax certificates tied to public services will enhance taxpayers’ compliance with tax regulations. However, the study is not exhaustive as it specifically focused on a tax enforcement tool in a developing economy. Practical implications: It is therefore recommended that all obstacles around issuance of tax certificates, especially in developing economies, should be surmounted by the government through its tax authority. Originality/value: The study is unique in its approach and population by considering tax officers within South West states in Nigeria.